Pengaruh Arus Kas Investasi, Arus Kas Operasi, dan Market Value Added Terhadap Return Saham - Sahfasat, Vina Martiani; Nurmala, Putri (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2022)
This study aims to determine the effect of investment cash flow, operating cash flow and market value added on stock returns. The data used is secondary data, using quantitative methods and panel data regression models with the help of the eviews 10 program to obtain a comprehensive picture of the relationship between one variable and another. The sample in this study consisted of 26 property and real estate sub-sector companies listed on the Indonesia Stock Exchange for 5 years from 2016-2020 with purposive sampling as the sampling method. The results showed that the variables of Investment Cash Flow and Operating Cash Flow had a significant effect on stock returns partially at the level of significance less than 0.05. Meanwhile, Market Value Added does not have a significant effect partially.